Best practice in primary care pathology: review 1. Issue 10 (27th September 2005) - Smellie, W S A; Wilson, D; McNulty, C A M; Galloway, M J; Spickett, G A; Finnigan, D I; Bareford, D A; Greig, M A; Richards, J
Abstract : This first best practice review examines four series of common primary care questions in laboratory medicine, namely: (i) measurement and monitoring of cholesterol and of liver and muscle enzymes in patients in the context of lipid lowering drugs, (ii) diagnosis and monitoring of vitamin B12/folate deficiency, (iii) investigation and monitoring of paraprotein bands in blood, and (iv) management of Helicobacter pylori infection. The review is presented in a question–answer format, referenced for each question series. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents, and evidence based medicine reviews, supplemented by MEDLINE EMBASE searches to identify relevant primary research documents. They are not standards but form a guide to be set in the clinical context. Most are consensus rather than evidence based. They will be updated periodically to take account of new information.